Research on manufacturing energy consumption optimization platform technology based on knowledge-base - Weiwei YANG; Sining WANG; Guide ZHENG; Yaqiong SONG (Dianxin kexue)
China’s manufacturing industry accounts for the largest proportion of the economy and involves a huge scale.It is of practical significance for enterprises to gradually realize energy consumption optimization through digital technology.Taking automobile manufacturing as an example, a scheme of energy consumption optimization based on knowledge-base was proposed, including the analysis of the characteristics of energy consumption in manufacturing industry, the key technologies of energy consumption optimization and the presentation of application practice.Starting with the production equipment of the enterprise, the law affecting energy consumption was found and a knowledge-base was build through the information of manufacturing execution system and equipment operation status of the enterprise, and the optimization of energy consumption was realized through machine learning algorithms such as neural network and correlation analysis.